Evidence-Based Treatment and Outcomes of Tibial Bone Stress Injuries: Current Concept Review - Jasty, Naveen; Dyrek, Paige; Kaur, Japsimran; Kathryn E. Ackerman; Kraus, Emily; Heyworth, Benton (Journal of the Pediatric Orthopaedic Society of North America, 2021)
Bone stress injury (BSI) of the tibia, a spectrum of impairments that include conditions commonly referred to as medial tibial stress syndrome (MTSS), tibial stress reaction, and tibial stress fracture, is relatively common in athletes of various ages and levels of competition. While simple rest from the offending activities remains the primary method of treatment, identification of nutritional, hormonal, and biomechanical risk factors is crucial to prevent persistent or recurrent injury. Perhaps the most basic and important mechanical risk factor, especially in those with chronic or recurrent injury, may be abnormalities in gait and ankle flexibility, which can range from subtle to severe. While magnetic resonance imaging-based (MRI) injury grading can provide a framework for expected healing time, treatment must be individualized and evolution of a patient’s symptoms should guide the progression to return to sport after a prescribed period of rest. The vast majority of tibial BSIs can be managed nonoperatively and surgery is largely reserved for those who have undergone exhaustive conservative management without success, those with multiple recurrences, or high-level competitive athletes with the most severe grades of injury. The current review aims to highlight current concepts in the treatment of tibial BSI, with a particular focus on the high-risk population of adolescent athletes.